2020
DOI: 10.12701/yujm.2020.00248
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization-inducing potentials of calcium silicate-based pulp capping materials in human dental pulp cells

Abstract: Background: This study was performed to provide a long-term bacterial seal through the formation of reparative dentin bridge, calcium silicate-based pulp capping materials have been used at sites of pulpal exposure. The aim of this study was to evaluate the mineralization-inducing potentials of calcium silicate-based pulp capping materials (ProRoot MTA [PR], Biodentine [BD], and TheraCal LC [TC]) in human dental pulp cells (HDPCs). Methods: Specimens of test materials were placed in deionized water for various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Research undertaken on cement extracts revealed no difference between ProRoot MTA and Biodentine with both groups exhibiting improved mineralization (Manaspon et al, 2021; Paula et al, 2019) whilst other studies reported a greater viability of HDPCs exposed to Biodentine cement extract in comparison with ProRoot MTA after 1 and 3 days (Kang, 2020). After 72 h, Biodentine had a significantly greater number of viable cells compared with MTA Angelus and ProRoot MTA using the Alamar Blue assay.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Research undertaken on cement extracts revealed no difference between ProRoot MTA and Biodentine with both groups exhibiting improved mineralization (Manaspon et al, 2021; Paula et al, 2019) whilst other studies reported a greater viability of HDPCs exposed to Biodentine cement extract in comparison with ProRoot MTA after 1 and 3 days (Kang, 2020). After 72 h, Biodentine had a significantly greater number of viable cells compared with MTA Angelus and ProRoot MTA using the Alamar Blue assay.…”
Section: Resultsmentioning
confidence: 99%
“…However, MTT assay revealed no significant differences in cell viability amongst the three materials and the negative control after 72 h (Poggio et al, 2014), suggesting the specific evaluation methods may also influence the result. Alkaline phosphatase (ALP) activity was lower in cells cultured with Biodentine compared with ProRoot MTA, whilst a similar pattern of mineralization-related gene expressions was observed (Widbiller et al, 2016) and the opposite was observed in another study (Kang, 2020). Both materials upregulated the expression of DSPP at 14 and 21 days (Widbiller et al, 2016).…”
Section: Cellular Studiesmentioning
confidence: 86%
See 2 more Smart Citations
“…When tested in contact with human dental pulp stem cells, to assess cell proliferation, viability mineralization potential and morphology, Biodentine exhibited adequate biological characteristics (133, 134) even when employing advanced cell culture models (135). The cells adhered well to the material surface (136) and the material extracts exhibited cell proliferation and expression as well (137)(138)(139). A calcific bridge was shown in animal studies employing Biodentine as pulp preservation material (140)(141)(142).…”
Section: Dressing the Dentinementioning
confidence: 99%